Single cell transcriptomics reveals recent CD8T cell receptor signaling in patients with coronary artery disease - Iqneibi, Shahad; Saigusa, Ryosuke; Khan, Amir; Oliaeimotlagh, Mohammad; Armstrong Suthahar, Sujit Silas; Kumar, Sunil; Alimadadi, Ahmad; Durant, Christopher P.; Ghosheh, Yanal; McNamara, Coleen A.; Hedrick, Catherine C.; Ley, Klaus (Frontiers in Immunology, 2023)
Coronary artery disease (CAD) is a major cause of death worldwide. The role of CD8+ T cells in CAD is unknown. Recent studies suggest a breakdown of tolerance in atherosclerosis, resulting in active T cell receptor (TCR) engagement with self-antigens. We hypothesized that TCR engagement would leave characteristic gene expression signatures. In a single cell RNA-sequencing analysis of CD8+ T cells from 30 patients with CAD and 30 controls we found significant enrichment of TCR signaling pathways in CAD+ subjects, suggesting recent TCR engagement. We also found significant enrichment of cytotoxic and exhaustion pathways in CAD cases compared to controls. Highly significant upregulation of TCR signaling in CAD indicates that CD8 T cells reactive to atherosclerosis antigens are prominent in the blood of CAD cases compared to controls.